(untitled) (Journal of Parents and Teachers, 2014)
Wanting to be part of a group or, what is the same, the meaning of belonging can lead to conduct or actions of all kinds. So, when we have to change our way of being and even our own self, when being with a group or with a person implies an exclusion from another sector or when to have fun we need to attack or resort to violence... The concepts of friendship, justice and freedom are "altered and damaged".